How Day School Teachers Perceive Their Working Conditions: A National Study. Issue 2 (3rd April 2017) - Tamir, Eran; Pearlmutter, Nili; Feiman-Nemser, Sharon
ABSTRACT: Induction and mentoring are widely considered in the United States and in the Organization for Economic Co-operation and Development (OECD) countries as a basic universal and critical intervention for a successful launch of new teachers. Based on an expanded set of survey data, this article focuses on how Jewish day schools offer professional support and learning opportunities from the head of school, the administration, colleagues, parents, and the school community and how useful teachers perceive these resources to be. This study reveals that less than half of all teachers in the schools surveyed report participating in formal induction programs and believe their schools take the learning needs of new teachers seriously. Schools would do well to attend to this aspect of teacher support and consider the systems and structures that do (or do not) exist to help orient, support, and develop new teachers.